2011
DOI: 10.1016/j.neuroscience.2011.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of visual vertical judgments: early and late brain mechanisms as revealed by high-density electrical neuroimaging

Abstract: Abstract-Constructing and updating an internal model of verticality is fundamental for maintaining an erect posture and facilitating visuo-spatial processing. The judgment of the visual vertical (VV) has been intensively studied in psychophysical investigations and relies mainly on the integration of visual and vestibular signals, although a contribution of postural and somatosensory signals has been reported. Here we used high-density 192-channel evoked potential (EP) mapping and distributed source localizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 99 publications
7
44
1
5
Order By: Relevance
“…These dependent variables were then subjected to statistical analysis using unpaired t tests with single trials as repeated measures. A similar analysis procedure has previously been applied to study a wide variety of cognitive processes in healthy subjects [such as perception (Lopez et al 2011), attention (Plomp et al 2009), social interaction (Thirioux et al 2010(Thirioux et al , 2014] as well as in clinical populations (Michel and Murray 2012).…”
Section: Erp Mappingmentioning
confidence: 99%
“…These dependent variables were then subjected to statistical analysis using unpaired t tests with single trials as repeated measures. A similar analysis procedure has previously been applied to study a wide variety of cognitive processes in healthy subjects [such as perception (Lopez et al 2011), attention (Plomp et al 2009), social interaction (Thirioux et al 2010(Thirioux et al , 2014] as well as in clinical populations (Michel and Murray 2012).…”
Section: Erp Mappingmentioning
confidence: 99%
“…In the second analysis step we performed statistical analysis and verified the presence of a given EP map as identified in the group-averaged data in the EPs of the individual participants. This is done by means of a fitting procedure based on the spatial correlation between template maps obtained from the group-averaged EPs data and the individual participants' data (Lopez et al, 2011). Thus, the dominant EP maps, as identified by the segmentation procedure in the group-averaged data (analysis step 1), were fitted to the EPs of each individual participant (analysis step 2).…”
Section: Sep Analysismentioning
confidence: 99%
“…For the effect of hemianopia, we have previously considered two main hypotheses, which could be either specific [12] or related to the presence of an associated posterior lesion. The importance of the posterior cortex in the SV task has been confirmed by a recent study in healthy subjects [28]. High-density electrical neuroimaging revealed that the SV task elicited early activation of the temporo-occipital area and later activation of both the temporo-occipital and parieto-occipital regions.…”
Section: Discussionmentioning
confidence: 61%